FEASIBILITY AND MARKET POTENTIAL ANALYSIS OF VANAMEI SHRIMP CULTIVATION ON HOUSEHOLD SCALE: CASE STUDY POKDAKAN MAWAR LESTARI, PANGKALPINANG - Ufi Ayu Wulandari; Ipung Hidayat; Tanisya Apindri; Ardiansyah Kurniawan (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Vannamei shrimp is a fishery cultivation commodity that has high economic value and has a global market. Shrimp can be cultivated on a household scale and have been developed on Bangka Island. One of the household scale shrimp cultivation business actors is Pokdakan Mawar Lestari which is located in Semabung Lama, Bukit Intan district,Pangkalpinang city, Bangka Belitung Islands Province. It is necessary to study the feasibility and development potential in Bangka Belitung. Vanamei shrimp cultivation on a household scale uses a tarpaulin pond measuring 17 x 14m2. Shrimp can reach sizes according to market demand with a maintenance period of 110-120 days. Shrimp marketing is carried out through holding companies and local markets. Household scale shrimp cultivation is profitable and has the potential to be applied in other areas on Bangka Islands. Handling of cultivation waste needs to be a concern so that economic benefits do not result in environmental losses.